The Effect of Using PQRST (Preview, Question, Read, Summarize, Test) Strategy Toward Students’ Reading Comprehension at Second Grade SMKS Teknologi YPL Lirik - Haprianda, Thika; Wahyuningsih, Destri (ENJEL: English Journal of Education and Literature, 2025)
study aims to determine the effect of the PQRST (Preview, Question, Read, Summarize, Test) strategy on the reading ability of class XI students of SMKS Teknologi YPL Lirik. The study used an experimental method with two classes: the experimental class using the PQRST strategy and the control class using the Problem Based Learning (PBL) method. The results of the pre-test and post-test were analyzed using normality, homogeneity, and t-test tests with the help of SPSS software. The results of the analysis showed that the PQRST strategy had a significant effect on students' reading comprehension. The experimental class showed a higher increase in average scores than the control class, proving the effectiveness of this strategy in improving students' reading ability.